2019
DOI: 10.1016/j.redox.2019.101300
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of reactive isolevuglandins in mitochondrial dysfunction and inflammation

Abstract: Inflammation is implicated in cardiovascular diseases, acute kidney injury, lung and heart failure, which represent major causes of morbidity and mortality in Western Societies. Despite use of multiple drugs, both chronic and acute inflammation is still remaining a major health burden. Inflammation produces highly reactive dicarbonyl lipid peroxidation products, isolevuglandins (isoLG) which reacting with lysine residues of proteins covalently modify and cross‐link proteins. Mitochondrial dysfunction has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 52 publications
2
7
0
Order By: Relevance
“…Furthermore, our findings highlight the critical role of succinate and long-chain fatty acids in kidney energy metabolism. We recently showed that 58% of glutamate-driven respiration was complex IIdependent [19]. Kidney mitochondria adapt to the high energy demands by diverting the mitochondrial metabolite flux to succinate to feed the Complex II-mediated respiration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, our findings highlight the critical role of succinate and long-chain fatty acids in kidney energy metabolism. We recently showed that 58% of glutamate-driven respiration was complex IIdependent [19]. Kidney mitochondria adapt to the high energy demands by diverting the mitochondrial metabolite flux to succinate to feed the Complex II-mediated respiration.…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen Monitor [12,14]. The respiration rates of kidney mitochondria were measured using Fluorescence Lifetime Micro Oxygen Monitoring System (Instech Laboratories, Inc.) [19].…”
Section: Measurements Of Mitochondrial Respirationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ngwenyama et al ( 2021 ) showed that myocardial oxidative stress triggers the generation of reactive isolevuglandin molecules that act as cardiac antigens to stimulate the T cell receptor (Ngwenyama et al 2021 ) to promote the development of heart failure (May-Zhang et al 2018 ), cardiac senescence, atherosclerotic and hypertensive heart disorders (Aschner et al 2021 ), including high salt-induced heart disease (Ruggeri Barbaro et al 2021 ). Data from both animal and human research (Ruggeri Barbaro et al 2021 ) have revealed that reactive isolevuglandin formation due to high salt diet (Ruggeri Barbaro et al 2021 ), myocardial oxidative stress (Ngwenyama et al 2021 ), pressure overload (Shang et al 2019 ), and lipopolysaccharide (LPS)-induced inflammation in mice (Mayorov et al 2019 ) can initiate the activation of monocytes, dendritic cell, and secretion of the proinflammatory cytokines TNF-α, IL-1β, IL-6, IL-17A (Dikalova et al 2020 ; Ruggeri Barbaro et al 2021 ), and reactive species (superoxide anions, and reactive nitrogen species) (Dikalova et al 2020 ). Thus, isolevuglandin may serve as a therapeutic target in the treatment of certain heart diseases.…”
Section: Contemporary View Of the Mechanisms Of Cardiac Inflammation ...mentioning
confidence: 99%
“…As organelles with important functions in eukaryotic cells, mitochondria mainly generate ATP, moderating apoptosis and oxidative stress reactions and exhibit dynamic changes. Their development and degradation, fusion and fission, and their quantity and morphology are precisely regulated and controlled based on changes in the environment where the cells are located (Zhou et al, 2017a,f;Chen S. et al, 2019;Mayorov et al, 2019;Simula et al, 2019). Mitochondrial dynamics include mitochondrial fission, fusion and mitophagy.…”
Section: Mitochondrial Dysfunction and Mitophagymentioning
confidence: 99%